Relationships between economic growth, foreign direct investment, and poverty in Africa - Saied Edrees, Abdelbagi Edrees (2017)
In the past years, Africa has experienced fast economic growth, unimproved business environment, low foreign direct investment inflows, and continuous high poverty rate. In fact, foreign direct investment (FDI) inflows in Africa are the lowest compared to other region's FDI inflows. Moreover, African countries are ranked at the bottom of the country-ranking list in term of quality of business environment. Therefore, the objectives of this study are to investigate the impact of foreign direct investment on economic growth in Africa, to estimate the impact of business environment on foreign direct investment, and to examine the determinants of poverty in the continent. The study covers the period from 2000 to 2014 in 50 African countries. The study utilizes panel annual data from World Bank, Mo Ibrahim Foundation, and United Nation Development Program. The study uses system Dynamic Generalized Method of Moments estimator (DGMM) because it takes control of endogeneity, and country specific effects problems that may arise in panel data estimations. The study found that foreign direct investment and business environment in addition to human capital, financial development, and political stability significantly contribute to economic growth of African countries. In addition, the results of the study reveal that business environment, economic growth, financial development, and institutions quality have important role in attracting the FDI inflows into African countries. Moreover, the study found that an improvement in economic growth, foreign aid, trade, and political stability significantly reduce poverty rate in the region. Overall results provide empirical evidence for African policy-makers to introduce policies that aim to attract more FDI inflows to enhance the economic growth of the region. Also, the results delivers empirical evidences for policy-makers to improve business environment that attracts more FDI inflows which generates economic growth. It also provides strong evidence for policymakers to improve financial services to facilitate trade and doing business in the continent. In addition, this study provides better foundation for African policy-makers to manage and introduce effective policies that would help in generating more economic growth and reduce poverty rate in Africa. Finally, this study has achieved the objectives of the thesis.